Zieve syndrome in acute alcoholic hepatitis. Issue 3 (2nd July 2020) - Achufusi, Ted George; Sandhu, Jasmine; Chahal, Japjot; Shepherd, Zachary; Mirchia, Kanish
Abstract: A 31-year-old woman presented with acute alcoholic hepatitis, jaundice, anemia, and hypertriglyceridemia following ethylene glycol poisoning. She had no previous history of anemia or gastrointestinal bleeding. Laboratory findings were consistent with acute hemolytic anemia. She was diagnosed with Zieve syndrome and was managed with supportive measures. Zieve syndrome is a rare occurrence with only a handful of published case reports. Although rare, the diagnosis should be on the differential in this subgroup of patients to avoid unnecessary and invasive diagnostic interventions.